John Boardman. The Greeks in Asia. - Erskine, Andrew (Journal of Greek Archaeology, 2017)
These two books are underpinned by the same essential theme, Greek influence in Asia, but they are very different. John Boardman is one of the leading historians of Greek art with a record of publication going back over fifty years, Elisabeth Katzy is at the other end of her academic career with this, her first book, a lightly-revised version of her Tübingen PhD thesis. Where Boardman covers the vast expanse from Turkey to China over the course of many centuries, Katzy’s focus is much narrower, a particular region of North Mesopotamia during the last three centuries BC. Both, however, make valuable contributions to our understanding of cultural interaction in the East.